The use of low-temperature plasma in a combined technology for the formation of wear-resistant boron-containing coatings; Surface and Coatings Technology; Vol. 389 - Klopotov A. A. Anatoly Anatoljevich; Ivanov Yu. F. Yury Fedorovich; Potekaev A. I. Aleksandr Ivanovich; Abzaev Yu. A. Yury Afanasjevich; Kalashnikov M. P. Mark Petrovich; Chumaevsky A. V. Andrey Valerjevich; Volokitin O. G. Oleg Gennadjevich; Teresov A. D. Anton Dmitrievich; Vlasov V. A. Viktor Alekseevich; Klopotov V. D. Vladimir Dmitrievich (2020, 2020)
Title screen